Association Between TNF-α-308, +489, −238 Polymorphism, and COPD Susceptibility: An Updated Meta-Analysis and Trial Sequential Analysis - Xia, Zhiyu; Wang, Yufei; Liu, Fu; Shu, Hongxin; Huang, Peng (Frontiers in Genetics, 2022)
The tumor necrosis factor alpha (TNF-α) polymorphism may play an important role in chronic obstructive pulmonary disease (COPD) susceptibility. However, the results are still inconclusive. Eligible studies were searched in Cochrane Library database, EMBASE, Pudmed, Web of science, China National Knowledge Infrastructure, and Wanfang database. Finally, a total of 27 case-control studies with 3473 COPD cases and 4935 controls were included in the present analysis. We also performed trial sequential analysis (TSA) to confirm our results. Overall, association between TNF-α-308G/A polymorphism and COPD susceptibility was identified in allelic model (A vs. G, OR = 1.21, 95%CI: 1.01–1.45, p = 0.04) when smoking status was not adjusted. In ethnicity subgroup analysis, we found that the TNF-α -308G/A polymorphism was associated to COPD among Asians (GA vs. GG, OR = 1.35, 95%CI: 1.04–1.77, p = 0.02) when smoking status was not adjusted. However, no significant association was found in Asian smokers or Caucasian smokers. In conclusion, our study suggest that TNF-α-308 GA genotype is related to COPD in the Asian population. In addition, the TNF-α+489G/A, - 238G/A variants do not increase the risk of COPD. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42021273980.